2004
DOI: 10.1111/j.1468-036x.2004.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Shareholder Value Creation in European M&As

Abstract: "This paper looks at the value generated to shareholders by the announcement of mergers and acquisitions involving firms in the European Union over the period 1998-2000. Cumulative abnormal shareholder returns due to the announcement of a merger reflect a revision of the expected value resulting from future synergies or wealth redistribution among stakeholders. Target firm shareholders receive on average a statistically significant cumulative abnormal return of 9% in a one-month window centred on the announcem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
144
2
16

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(188 citation statements)
references
References 37 publications
26
144
2
16
Order By: Relevance
“…Both of these results are smaller than the investors' reaction to domestic mergers over the same time period, suggesting some apprehension to cross-border mergers. 10 This is consistent with Campa and Hernando's (2002) findings that the wealth effects of European cross-border mergers are less than the abnormal returns to domestic mergers, although contrary to the findings of Harris and Ravenscraft (1991) for US crossborder mergers.…”
Section: Cross-border Mergerssupporting
confidence: 53%
“…Both of these results are smaller than the investors' reaction to domestic mergers over the same time period, suggesting some apprehension to cross-border mergers. 10 This is consistent with Campa and Hernando's (2002) findings that the wealth effects of European cross-border mergers are less than the abnormal returns to domestic mergers, although contrary to the findings of Harris and Ravenscraft (1991) for US crossborder mergers.…”
Section: Cross-border Mergerssupporting
confidence: 53%
“…Grouping the research of performance into bidder and target sides, the target firm's performance is always positive (Roll, 1986;Campa and Hernando, 2004). But there still is no agreement on the performance of the acquirer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, some studies have found that the short-run performance of target firms is positive and significant (Bruner, 2002 andCampa andHernando, 2004). The positive value effect on target shares is logical as the bidders typically pay premiums to target shareholders in order to compensate them to give up control rights.…”
Section: Short-term Performance Of Cross-border Manda Activities Of Acqmentioning
confidence: 99%
“…A recent paper by Campa and Hernando (2004) suggests that barriers that are outside the control of banks play a role. Their study shows that the combined economic returns of acquirer and target (the combined cumulative abnormal returns of M&As) are typically lower in industries, such as banking, that until recently were under government control or are still or were most heavily regulated.…”
Section: • Information Asymmetries Between Domestic and Internationalmentioning
confidence: 99%
“…Selon une étude récente publiée par Campa et Hernando (2004), des barrières extérieures au contrôle des banques jouent un rôle en la matière. Il apparaît que la performance boursière combinée de l'acquéreur et de la cible (performance boursière combinée des fusions-acquisitions) est généralement inférieure dans les secteurs, comme le secteur bancaire, qui étaient jusque récemment, contrôlés par l'État, qui sont encore ou étaient les plus réglementés.…”
unclassified